Dinámica de las relaciones en las familias ensambladas en el municipio de Hatonuevo, Departamento de La Guajira (2021)
The development of this research project aims to analyze the dynamics family in the families assembled in the municipality of Hatonuevo, department of La Guajira arises from the importance that this type of family has been representing for society, even more so when there has been an increase in this type of family in recent years. In the Nowadays, it is very common to find cases where the formation of the family occurs after some case of widowhood, a single father and mother, or before the failure of a first marriage, the person is given the possibility of a second marriage where in addition to living together the spouse, there is a probable situation that he or she may have children as well. This generates a type of family known as assembled or rebuilt. To approach the study, the theoretical contributions of Aguilar (2017), Rodríguez (2017), Valdivieso (2015), Ares (2012), Minuchin (1986), among others